Transmembrane adenylyl cyclase regulates amphibian sperm motility through protein kinase A activation - O'brien Echeverría, Emma Dinorah (2011)
Sperm motility is essential for achieving fertilization. In animals with external fertilization as amphibians, spermatozoa are stored in a quiescent state in the testis. Spermiation to hypotonic fertilization media triggers activation of sperm motility. Bufo arenarum sperm are immotile in artificial seminal plasma (ASP) but acquire in situ flagellar beating upon dilution. In addition to the effect of low osmolarity on sperm motility activation, we report that diffusible factors of the egg jelly coat (EW) regulate motility patterns, switching from in situ to progressive movement. The signal transduction pathway involved in amphibian sperm motility activation is mostly unknown. In the present study, we show a correlation between motility activation triggered by low osmotic pressure and activation of protein kinase A (PKA). Moreover, this is the first study to present strong evidences that point toward a role of a transmembrane adenyl-cyclase (tmAC) in the regulation of amphibian sperm motility through PKA activation.